Morphological and functional characteristics of aging kidneys based on two‐photon microscopy in vivo. Issue 2 (28th November 2019) - Wu, Shulian; Guo, Hengchang; Horng, Hannah; Liu, Yi; Li, Hui; Daneshpajouhnejad, Parnaz; Rosenberg, Avi; Albanese, Christopher; Ranjit, Suman; Andrews, Peter M.; Levi, Moshe; Tang, Qinggong; et al.
Abstract: Age‐related kidney disease, which is chronic and naturally occurring, is a general term for a set of heterogeneous disorders affecting kidney structures and characterized by a decline in renal function. Age‐related renal insufficiency has important implications with regard to body homeostasis, drug toxicity and renal transplantation. In our study, two‐photon microscopy was used to image kidney morphological and functional characteristics in an age‐related rat model in vivo. The changes in morphology are analyzed based on autofluorescence and Hoechst 33342 labeling in rats with different ages. Structural parameters including renal tubular diameter, cell nuclei density, size and shape are studied and compared with Hematoxylin and Eosin histological analysis. Functional characteristics, such as blood flow, and glomerular filtration rate are studied with high‐molecular weight (MW) 500‐kDa dextran‐fluorescein and low‐MW 10‐kDa dextran‐rhodamine. Results indicate that morphology changes significantly and functional characteristics deteriorate with age. These parameters are potential indicators for evaluating age‐related renal morphology and function changes. Combined analyses of these parameters could provide a quantitative, novel method for monitoring kidney diseases and/or therapeutic effects of kidney drugs. Abstract : Age‐related kidney disease, which is chronic and naturally occurring, is a general term for a set of heterogeneous disorders affecting kidney structures and characterized by a decline in renal function. In our study, the morphological and functional characteristics of rat kidneys with different ages were studied in vivo using two‐photon microscopy.